The Impact of Leadership Style on Job Enrichment: AN empirical study in telecommunication companies (Damascus University Journal for the economic and Political sciences, 2024)
The aim of the research is to study the impact of leadership style on job enrichment by application in telecommunications companies,. the research relied on the descriptive approach and the analytical method, and used the questionnaire tool. 300 questionnaires were distributed to the telecommunications sector companies in the Syrian Arab Republic (STC-Syriatel -MTN), and 275 questionnaires were retrieved from them that can be analyzed using the SPSS program. The research reached To the most important results There is a significant effect of the reciprocal and transformational leadership style on job enrichment and also There are substantial differences between the respondents due to their demographic variables (age, years of experience) in terms of the relationship between leadership style and job enrichment and There are no significant differences between the respondents due to their demographic variables (gender, educational level, type of company) in terms of the relationship between leadership style and job enrichment.
Keywords: Transformational Leadership; Reciprocal Leadership; Job Enrichment; Telecommunications Companies